Perkembangan Pariwisata Di Daya Tarik Wisata Pantai Berawa Kabupaten Badung - Dipadewanda, I Made; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA; Vol 6 No 2 (2018): VOL 6, NO 2 (2018): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2019)
The research is conducted in Banjar Berawa/Desa Adat Berawa, nort Kuta district, B a dung Regency. The study purposes to know the impact of tourism growth to the society consumptive pattern in Berawa . The technique of the data collection use direct observation technique to the location, interviewing for informan, I.E.Bendesa Adat Berawa, Klian Desa Berawa, Klian Dinas Berawa, Klian Subak Tibubeneng Village, Local society, and documentation by taking photos. The data are analysed by using qualitative data analysis technique which are working based on data, searching and finding pat t ern, getting interesting data and deciding the data that will be ssuced. The technique of informants assigmnen is purposive sampling which is assigning the sample by using particular consideration so, deserves to be a sample. The data analysis includes with collection data, reduction data, displaying data, conclusion and  verivication. The r e s ult of the study shows the society point of view to the aconomy establishmemt of educational aspec of the society which is getting increase, society in Banjar Berawa are also starting to enterpreneurship by set up abussiness such as homestay and laundy. The point of view of society to the customary order is the society seens strong with the wealth that they have. The society fulfill their family neededs by taking many kends of occupation.   Keywords : Impact, tourism, consumptionpattern, society